Migration and Global Environmental Change: SR8: The possible impacts of high levels of climate change in 2060 and implications for migration - New M; Anderson, K.; Fung F; Thornton, Philip K. (Government Office for Science, 2011)
Anthropogenic climate change has the potential to affect nearly all aspects of society, both positively and negatively (IPCC, 2007a). One adaptation response to severe climate impacts is migration, either within or across national borders (e.g. McLeman and Smit, 2006; Tacoli, 2009; Bardsley and Hugo, 2010; Feng et al., 2010; Gemenne, 2011). Whether migration in response to climate change, or, more generally, environmental stress, is actually chosen as an adaptation option depends on many factors, discussed in more detail elsewhere (e.g. Julca and Paddison, 2010; Kolmannskog and Trebbi, 2010; Martin, 2010; Warner et al., 2010; Marchiori and Schumacher, 2011; Piguet, 2011). Indeed, where regional effects of climate change are beneficial, climate change may act as a pull rather than a push factor (Piguet, 2011).